Proteomics and Precision Medicine. Issue 7 (10th April 2019) - Ding, Chen; Qin, Zhaoyu; Li, Yan; Shi, Wenhao; Li, Lingling; Zhan, Dongdong; Yang, Wenjun
Abstract: During the last decade, great progress has been made in mass spectrometry rendering the identification of 6000 proteins in an hour and up to 10 000 proteins in half a day. The proteome has been widely applied in a variety of studies in the life sciences, for dissecting protein profiling, protein–protein interactions, post‐translational‐modification, etc. Since the improvement of the proteome screening efficiency and the decreasing of the cost in sample measurement, the growing requirement of deep application of proteomics has been raised recently in clinical research, foretelling an era in which proteomics will enable personally tailored therapies for patients. This review describes the cutting‐edge progression of next‐generation proteomics and highlights its potential in precision medicine in the future. Abstract : After decades of technological accumulation, biomedical and life sciences are embracing an era of "precision medicine based on the next generation of proteomics." People are able to feature high dimensional proteomes of different human samples within multiple dynamic conditions. By integrated‐omics subtyping analysis and the participation of large‐scale cohort, the personalized disease prevention and predictions are finally realizable.